The CNGRCLLII(KLAKLAK)2 peptide shows cytotoxicity against HUVECs by inducing apoptosis: An in vitro and in vivo study - Guanying Wang; Na Yuan; Shangke Huang; Lu Feng; Rui Han; Yujiao Zhang; Juan Ren; Min Meng; Xinhan Zhao (Tumor Biology, 2017)
Fibrinogen Asn-Gly-Arg motif can specifically recognize and bind to Aminopeptidase N (CD13) on vascular endothelial cells in newly formed tumor vessels. Adipose-derived stem cells can serve as ideal vectors for gene therapy because of their ability of migrating to tumor tissues. First, this study was aimed to design a new peptide (CNGRCLLII(KLAKLAK)2) named CNAK which contains cyclic Asn-Gly-Arg motif and test its biological activity against human umbilical vein endothelial cells. Second, we aimed to construct stably transfected adipose-derived stem cells which express the CNAK peptide and investigate their anti-angiogenic activity in vivo. Adipose-derived stem cells were employed to localize CNAK on vascular endothelial cells in tumors based on their homing property. First of all, the new peptide was synthesized, which effectively entered into CD13+ human umbilical vein endothelial cells and showed cytotoxicity against human umbilical vein endothelial cells. The peptide induced apoptosis of human umbilical vein endothelial cells in a time- and dose-dependent manner, inhibited the expression of Bcl-2, and promoted the expression of Caspase-3 in human umbilical vein endothelial cells. Furthermore, the migration and tube formation of human umbilical vein endothelial cells were inhibited by CNAK. Primary adipose-derived stem cells were then isolated and identified. Stably transfected adipose-derived stem cells which express CNAK peptide (CNAK-ASCs) were successfully established, and the migration of CNAK-ASCs was assessed. In vivo, CNAK-ASCs were found to inhibit the growth and angiogenesis of breast cancer xenografts. This effect may be through inhibiting the secretion of matrix metalloproteinase-2 and membrane type 1-matrix metalloproteinase in vivo. It was also found that CNAK-ASCs reduced the quantity of breast cancer stem cells in tumor tissues. Our data suggested that the new peptide CNAK containing Asn-Gly-Arg motif had anti-angiogenic activity in vitro and in vivo.